UPAYA MENINGKATKAN HASIL BELAJAR IPSSISWA MELALUI PENGGUNAAN MEDIA PETA DI KELAS VSD NEGERI 004 BUKIT DATUK DUMAI - Herlina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe students’ learning outcomes through the use of map media. The subjects of the study were fifth-grade students of SD 004 Bukit Datuk Dumai, and the research was conducted in two cycles. Improvements in learning outcomes were analyzed based on four categories, namely learning absorption, learning effectiveness, mastery learning completeness at both individual and classical levels, and overall learning achievement. The instruments used for data collection were oral tests and written tests in the form of worksheets administered after the learning process. The results showed that the average learning absorption reached 83%, which was categorized as very good, the learning effectiveness was categorized as very effective with an average score of 8.5, and the completeness of student learning outcomes reached 100%.